Pengaruh Inovasi Hijau dan Akuntansi Manajemen Lingkungan Terhadap Pertumbuhan Berkelanjutan - Fadhilah Nuraini Almushaly; Risa Nurmala Dewi (Mathematics Education Study Program, 2025)
This study aims to examine the influence of green innovation and environmental management accounting on sustainable growth. The population in this study is non-cyclical consumer sector companies that are listed on the Indonesia Stock Exchange in the 2020-2023 period. The data used is secondary data obtained from the company's financial statements through the www.idx.co.id website or the website of each company. This study uses a purposive sampling method with several criteria and obtained as many as 140 sample data. The method used in this study is a quantitative method with a multiple linear regression approach and Moderated Regression Analysis (MRA) technique. The results show that the green innovation variable has a negative effect on sustainable growth, and environmental management accounting has a positive effect on sustainable growth.